Concept of situational management of safety critical infrastructure of state - Michał Wiśniewski (Foundations of Management, 2016)
This article presents a synthesis of knowledge about safety management procedures for critical infrastructure (CI) in the context of risk management theory and the provisions of the Polish law on emergency management of 26 April 2007. In this paper, the inadequacy of the accepted procedures at present is highlighted, as well as their continuous improvement and adaptation to prevailing political, legal, social and economic conditions. It proposes using the concept of scenario approach and situational management approach and technique analysis of interconnected decision areas (AIDA) and casebased reasoning (CBR) to develop integral situational resource model CI. The considerations presented in this paper lead to a proposed a new method for predicting, preventing and responding to emerging crises within the CI.
Keywords: 650; critical infrastructure; situational approach; analysis of interconnected decision areas; case based reasoning; crisis management; threat; risk assessment; scenario of events; a domino effect; flat and hierarchical decision problem